Cover Image. Issue 3 (21st March 2021) - Yamamoto, Hiroyuki; Sawada, Takahiro; Takaya, Tomofumi; Kawai, Hiroya; Yasaka, Yoshinori
Abstract : The cover image is based on the Case Report Novel strategy for ostial left anterior descending artery acute myocardial infarction: Combined treatment with directional coronary atherectomy followed by drug‐coated balloon angioplasty by Hiroyuki Yamamoto et al., https://doi.org/10.1002/ccr3.3659 .